ANALISIS LINGKUNGAN SOSIAL EKONOMI PENGELOLAAN PERKEBUNAN KELAPA SAWIT BERKELANJUTAN BERDASARKAN KRITERIA ISPO PT. TAPIAN NADENGGAN - Dewi Agustina; Hariyadi Hariyadi; Saharuddin Saharuddin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Indonesian’s Goverment has obliged palm oil plantation companies to produce sustainable palm oil by the regulation from ministry of Agriculture No. 19/2011 about guidelines for Indonesian Sustainable Palm Oil (ISPO). This research aimed to study the plantation management of PT. Tapian Nadenggan from their existing socio-economic aspects, then to analyze its sustability according to ISPO’s principles and creteria. The method was done by collecting primary data through interview(in general as well as intensive interview with key spekers), distributing questionnaires, executing field observation, taking respondent by purposive sampling method. Secondary data was obtained from the company’s data and literature review. The analysis result shows that the process of the land approval and the company’s responsibility toward their employess are convenient with ISPO’s principles and criteria. While for the execution of plasma plantation, the company’s social responsibility toward local culture development has not been fulfilled yet. Keywords: ISPO, palm oil, social economic